TOWARDS AN OPEN BIOMETRIC ONTOLOGY - Bača, Miroslav; Schatten, Markus; Rabuzin, Kornelije (Journal of Information and Organizational Sciences, 2007)
Over the last decade we faced a great number of publications in the field of biometrics. Many new biometric methods, techniques, models, metrics and characteristics were proposed. Due to this explosion of research, scientific and professional papers certain inconsistencies in terminology. What some authors call a biometric method, others call model, system or even characteristic. There wasn’t enough effort in creating a unique systematization and categorization which would approach the stated issues and open new areas of research. We argue that it is possible to approach biometrics in a narrower and in a broader perspective. We observed biometrics in the narrower perspecive and created a unique framework for the systematization and categorization of biometric methods, models, characteristics and patterns based on a general biometric system. This systematization is a fundamental step forward towards the creation of an open biometrics ontology.